Physiological quality of algaroba seeds recovered from faeces of mules - Gonçalves, Gerlândio Suassuna; Andrade, Leonaldo Alves; Gonçalves, Edilma Pereira; Oliveira, Lamartine Soares Bezerra; Dias, Jobson Targino (Semina: Ciências Agrárias, 2013)
Preventing expansion into areas not yet infested is a priority standard for controlling mesquite. The contamination of other areas occurs through the flocks (endozoochory), which disperse the seeds in different areas to consume fruits, facilitating the emergence of new stands of invasive plant. This research was carried out with the objective to determine the transit time through the gastrointestinal tract (GIT), viability and vigor of mesquite seeds (Prosopis juliflora (Sw.) DC.), recovered in the faeces of mules. Three adult mules were confined in stalls, being daily supplied to each of them as part of their diet, a kilogram of fruits of this invasive specie. The excrements were collected, placed on sieves and washed with running water to hold the seeds. The following variables were evaluated: percentage of seeds excreted, percentage of seeds with radicle emission and physiological quality of seeds. The mules, to consume the fruits of P. juliflora, effectively contribute to the advancement of biological invasion, being necessary to receive appropriate management not to act as dispersers of that invasion. The physiological quality of seeds of P. juliflora has not diminished with time spent in GIT. To clean the digestive tract of mules after consumption of fruits of that invasion are required at least 10 days. In the field, about 20% of the excreted seeds can be preserved viable in the faeces for longer than six months.